2015
DOI: 10.1021/acs.biochem.5b00064
|View full text |Cite
|
Sign up to set email alerts
|

Apoprotein Structure and Metal Binding Characterization of a de Novo Designed Peptide, α3DIV, that Sequesters Toxic Heavy Metals

Abstract: De novo protein design is a biologically relevant approach that provides a novel process in elucidating protein folding and modeling the metal centers of metalloproteins in a completely unrelated or simplified fold. An integral step in de novo protein design is the establishment of a well-folded scaffold with one conformation, which is a fundamental characteristic of many native proteins. Here, we report the NMR solution structure of apo α3DIV at pH 7.0, a de novo designed three-helix bundle peptide containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 79 publications
0
43
0
1
Order By: Relevance
“…Previous studies have demonstrated that α 3 D IV , α 3 D IV -H72C, and α 3 D IV -L21C are well-folded, three-helix bundle proteins. 7,8,27 Furthermore, circular dichroism spectra indicated that the structure of the peptide is not drastically altered by the presence of iron and that iron binding stabilizes the peptide slightly (Figure S1). Fe(II) binding titrations as monitored by UV–vis spectroscopy showed that the peptide binds Fe(II) in a pH-dependent fashion with a K D of 6.3 μ M at pH 8.5 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that α 3 D IV , α 3 D IV -H72C, and α 3 D IV -L21C are well-folded, three-helix bundle proteins. 7,8,27 Furthermore, circular dichroism spectra indicated that the structure of the peptide is not drastically altered by the presence of iron and that iron binding stabilizes the peptide slightly (Figure S1). Fe(II) binding titrations as monitored by UV–vis spectroscopy showed that the peptide binds Fe(II) in a pH-dependent fashion with a K D of 6.3 μ M at pH 8.5 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…45 However, additional mutations such as those in the α 3 DChC2 sequence led to proteins of markedly inferior thermodynamic stability. It was also considered that, for this reason, the α 3 DChC2-designed hydrophobic box was imperfectly constraining the metal binding site, causing the red copper spectral properties.…”
Section: Introductionmentioning
confidence: 99%
“…The preassembled fold of α 3 D offers facile incorporation of a mixed-ligand site within a de novo designed scaffold. Utilizing the structure of α 3 DIV 16 as a foundation, we designed three distinct constructs, designated as α 3 D-core (CR), -chelate (CH), and -chelate-core (ChC) (Table 1). Our goal was to assess if the physical properties (e.g., absorption λ max at 600 nm, compressed A ∥ , short Cu–S(Cys) bond, and E ° value >180 mV) of a metal center that is naturally observed in a β -barrel fold can be achieved in the antiparallel three-helix bundle fold of α 3 D. Ultimately, the lessons learned from this work will provide the foundation to study long-rate ET reactions within a de novo designed framework and develop bifunctional/bimetallic constructs that contain a catalytic and an ET center, such as in copper nitrite reductase.…”
Section: Introductionmentioning
confidence: 99%